2010
DOI: 10.1177/548.6519
|View full text |Cite
|
Sign up to set email alerts
|

Expression of c-kit in Common Benign and Malignant Breast Lesions

Abstract: Combined overexpression of c-kit and p63 is indicative of benign breast lesions. In contrast, there is reduced expression of c-kit in in situ and invasive breast carcinomas, with simultaneous overexpression in the stromal cells. This suggests that c-kit may play a role in breast cancer progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 29 publications
2
24
0
1
Order By: Relevance
“…Similar results were also reported by Kondi-Pafiti et al (2010) and Amin et al (2012). Similar results were also reported by Kondi-Pafiti et al (2010) and Amin et al (2012).…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were also reported by Kondi-Pafiti et al (2010) and Amin et al (2012). Similar results were also reported by Kondi-Pafiti et al (2010) and Amin et al (2012).…”
Section: Discussionsupporting
confidence: 92%
“…21,22 As for scoring criteria, we used a 1% cutoff in view of the fact that CD117 is not normally expressed in breast stromal cells. 23 Hence, even a low percentage of protein expression could indicate an abnormal state. This is exemplified by our study in which cases that were CD117 positive on immunohistochemistry demonstrated a low percentage of positive cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified c-Kit-expressing interstitial cells in the stromal compartment of human prostate [7779]. Altered patterns of c-Kit expression have been reported in benign lesions of prostate and breast tissues [80, 81]. It has been shown that the c-Kit expression and number of c-Kit(+) interstitial cells were significantly higher in BPH than those of the normal prostate.…”
Section: Stem Cell In Benign Prostate Hyperplasia (Bph)mentioning
confidence: 99%